Inventory Control Analysis of PT Gunung Sugih Tapioca Flour - Hilda Febrina; Erlina (PT FORMOSA CENDEKIA GLOBAL, 2023)
In 2022, PT Gunung Sugih faced challenges managing raw material inventory, leading to high total costs. This study investigates if inventory control serves as an effective policy for optimal levels and cost reduction. Employing observation, interviews, and documentation, the research employs the Economic Order Quantity (EOQ) method to assess orders, safety stock, reorder points, and total inventory costs. Results reveal the EOQ method minimizes costs, suggesting 281 tons for safety stock and 611 tons for reorder points, contrary to the company's undefined values. EOQ method yields a total inventory cost of Rp.58.18 million, saving 28.54% compared to the company's policy (Rp.81.42 million). The study advocates EOQ as a more optimal approach for cassava raw material inventory control